Evaluation of the safety profile of endoscopic pyloromyotomy by G-POEM: a French multicenter study. (October 2022) - Baret, Florian; Jacques, Jeremie; Pioche, Mathieu; Albouys, Jeremie; Vitton, Véronique; Vanbiervliet, Geoffroy; Debourdeau, Antoine; Barthet, Marc; Gonzalez, Jean-Michel
Background: Gastric per oral endoscopic esophageal myotomy (G-POEM) is a promising procedure to treat refractory gastroparesis. The safety profile of G-POEM is an important topic because gastroparesis is a functional pathology, with a procedure whose effectiveness is between 50 and 65% depending on the studies. Objectives: We present this retrospective multicenter study, with the aim of establishing a safety profile, focusing on serious adverse events (AEs). Design: This was a multicenter observational cohort study conducted in five French expert centers. Methods: All patients who underwent G-POEM for refractory gastroparesis between 2015 and 2021 were included for analysis. AEs were classified into per endoscopic, early postoperative, and late postoperative, up to 1 month. Their severity was assessed using Dindo–Clavien and American Society for Gastrointestinal Endoscopy classification. The primary objective was to evaluate the rate of G-POEM severe AEs. Secondary objectives were to document other postoperative AEs, and to identify predictive factors. Results: In all, 217 patients were included: 81 men and 136 women, mean age 52 ± 17 years. The average procedural time was 44 ± 14 min (12–78). The average hospital stay was 3.7 ± 2.3 days. The AEs rate classified as Clavien–Dindo ⩾3 was 0.4% (one delayed bleeding requiring blood transfusion and endoscopic management). There were no deaths or patients admitted to intensive care unit. The rates of mucosotomy and capnoperitoneum were 3.7 and 1.8%, respectively, without clinical consequences. Most patients (81.5%) did not experience any AE. Three cases of dumping syndrome occurred, quickly managed by dietary measures. Conclusion: Our study confirms the safety of G-POEM with less than 0.5% of serious AEs, medically managed. This outcome makes this a procedure to have a good benefit–risk ratio.